Improved Functional Expression of Cytochrome P450s in Saccharomyces cerevisiae Through Screening a cDNA Library From Arabidopsis thaliana - Jiang, Lihong; Dong, Chang; Liu, Tengfei; Shi, Yi; Wang, Handing; Tao, Zeng; Liang, Yan; Lian, Jiazhang (Frontiers in Bioengineering and Biotechnology, 2021)
Cytochrome P450 enzymes (P450s) are a superfamily of heme-thiolate proteins widely existing in various organisms and play a key role in the metabolic network and secondary metabolism. However, the low expression levels and activities have become the biggest challenge for P450s studies. To improve the functional expression of P450s in Saccharomyces cerevisiae, an Arabidopsis thaliana cDNA library was expressed in the betaxanthin-producing yeast strain, which functioned as a biosensor for high throughput screening. Three new target genes AtGRP7, AtMSBP1, and AtCOL4 were identified to improve the functional expression of CYP76AD1 in yeast, with accordingly the accumulation of betaxanthin increased for 1.32-, 1.86-, and 1.10-fold, respectively. In addition, these three targets worked synergistically/additively to improve the production of betaxanthin, representing a total of 2.36-fold improvement when compared with the parent strain. More importantly, these genes were also determined to effectively increase the activity of another P450 enzyme (CYP736A167), catalyzing the hydroxylation of α-santalene to produce Z-α-santalol. Simultaneous overexpression of AtGRP7, AtMSBP1, and AtCOL4 increased α-santalene to Z-α-santalol conversion rate for more than 2.97-fold. The present study reported a novel strategy to improve the functional expression of P450s in S. cerevisiae and promises the construction of platform yeast strains for the production of natural products.